Virtual simulation of communication between KUKA robot and PLC. (September 2020) - Shen, Bin; Yang, Zhihang; Wang, Yanwu
Abstract: Virtual simulation can effectively provide the training environment for the robot. It can solve many problems in robot practice, such as complex equipment, high price and so on. Virtual simulation and communication of KUKA robot can increase more possibilities. Based on the study of its trajectory planning and kinematics, this paper further increases the research content of virtual policy. This paper takes uniy3d virtual reality engine as the development platform, and studies the virtual motion simulation and control of industrial robot from the perspective of interaction between virtual robot and real robot,